Architectural acoustics - Long, Marshall (Academic Press, 2014)
"Presents a thorough technical overview of the discipline, from basic concepts to specific design advice. Beginning with a brief history, it reviews the fundamentals of acoustics, human perception and reaction to sound, acoustic noise measurements, noise metrics, and environmental noise characterization."--Publisher's description.